PEMBERDAYAAN ANAK DI KAWASAN PESISIR MELALUI PELATIHAN ME’ERAJI BERBASIS AI SEBAGAI UPAYA PELESTARIAN BUDAYA LOKAL - Ayu Hidayanti Ali; Eka Sartika (Journal of Community Services on Multidisciplinary Sciences, 2025)
The coastal area of Teluk Tomini holds a valuable cultural heritage, including the unique and meaningful tradition of Me’eraji. However, with the passage of time and the wave of globalization, this tradition is at risk of fading due to the declining interest of younger generations in learning local culture. One effective way to preserve and revive the Me’eraji tradition is through AI-based Me’eraji training. This community service activity began with a socialization program for the residents of Sipatana Village, Buntulia District. Following this, AI-based Me’eraji training was conducted in collaboration with the village youth organization. By utilizing Artificial Intelligence technology, innovative and creative simulations and training sessions were developed. The outcome of this training resulted in changes that aligned with the predetermined targets, such as increasing children's interest in learning the Me’eraji tradition and enhancing their knowledge of AI technology. As children's interest in learning Me’eraji grew, so did their appreciation and understanding of local culture.